Idiopathic spontaneous pneumothorax secondary to catamenial pneumothorax not associated with endometriosis: Case report - Diaz- Romero, Johann (2023)
Idiopathic spontaneous pneumothorax is a rare cause of pneumothorax, if non-pulmonary causes such as catamenial pneumothorax and/or catamenial pneumothorax not associated with endometriosis are attributed to it, this condition becomes even rarer. The therapeutic approach is closely related to the control of the complications generated by the pneumothorax. The following is the case of a 34-year-old female patient, who debuts with her first episode of spontaneous pneumothorax, which is presumed to have catamenial characteristics due to the coincidence with her menstrual cycle.